Hyperstable Perovskite Solar Cells Without Ion Migration and Metal Diffusion Based on ZnS Segregated Cubic ZnTiO3 Electron Transport Layers. Issue 3 (18th January 2021) - Han, Faming; Wu, Yazhuo; He, Ruiqin; Hui, Yong; Yin, Jun; Zheng, Lansun; Wu, Binghui; Zheng, Nanfeng
Abstract : Perovskite solar cells (PSCs) have attracted great interest in recent decade, however, stability issue and large‐scale application still remain as roadblocks to their practical applications. To settle aforementioned issues, metal diffusion and ion migration should be controlled to improve long‐term operational stability. Herein, cubic zinc metatitanate (ZTO) is optimized and improved by segregating with surface sulfidation. The sulfurized electron transporting layer, label as ZTO‐ZnS, based PSCs achieved an amazing power conversion efficiency (PCE) of 21.3%. A large‐area module (8.0 cm 2 active area) based on ZTO‐ZnS is also developed with 15.9% PCE. Furthermore, combining with inorganic CuI hole transporting layer and carbon counter electrode, metal diffusion, and ion migration effect are eliminated drastically in ZTO‐ZnS‐based PSCs. The combined PSC devices can easily keep more than 85% initial PCE after 1 000 h at 85 °C in air with a relative humidity of 85% under maximum power point and continuous AM 1.5G illumination. The persistence in stability is investigated and revealed fully by energy dispersive spectrometer analysis, attributing to the PSC structure which blocks the metal diffusion and ion migration in the devices. A big step forward industrialization and commercialization for PSCs is made. Abstract : ZnS interlayer has been introduced onto cubic ZnTiO3 electron transporting layer (ETL) of perovskite solar cells (PSCs) which not only blocked ion migration but also improved electron transfer across the perovskite–ETL interface, thus enhancing both stability and efficiency of the PSCs. Combining with CuI hole transporting layer and carbon electrode, the PSCs showed a remarkable superiority in stability.